Sperm DNA Integrity in Absolute Teratozoospermia Patients and its Impact on Assisted Reproductive Technology Outcome - Faris, Dina (AUC Knowledge Fountain, 2023)
Sperm DNA Fragmentation (SDF) is a common cause of male infertility, although it is underdiagnosed due to lack of routine testing. High levels of SDF are reported in men with abnormal sperm morphology. However, the implications of such findings on live birth following Intracytoplasmic Sperm Injection (ICSI) have not been studied in absolute teratozoospermia men (100% abnormal sperm morphology). In this prospective study, the severity of DNA damage was evaluated in absolute teratozoospermia patients and its impact on ICSI outcomes, particularly live birth rate. My study included 36 men with absolute teratozoospermia and 30 men with normal sperm. Real-time assessment of sperm morphology with 6600x magnification was used and the Sperm Chromatin Dispersion test was implemented to measure DNA fragmentation. The average SDF in absolute teratozoospermia patients was significantly higher (42.9%) compared to the normal semen group (24.6%). Normal SDF (30%). The pregnancy rate following ICSI in the control group was 67%, compared to 47% in the absolute teratozoospermia group. The miscarriage rate was 53% in the absolute teratozoospermia group compared to 25% in the control group. In the absolute teratozoospermia group, 20% achieved a live birth compared to 47% in the control group. Miscarriage and live birth outcomes in absolute teratozoospermia patients were remarkably compromised, which indicates that live birth assessment is fundamental in assisted reproduction research; pregnancy rate does not reflect the true chances of treatment success. Elevated levels of SDF are predominant in absolute teratozoospermia cases, which constitutes a detrimental impact on miscarriage and live birth rates following ICSI. To my knowledge, this is the first study to measure the live birth rate after ICSI in absolute teratozoospermia patients compared to controls based on the degree of sperm DNA fragmentation. Studying embryo quality, blastocyst formation, and pregnancy rate is not sufficient to show the true effect of SDF on the eventual outcome of embryos; for purposes of making clinical decisions, it is important to continue the study until a live birth is achieved. The present study is also the first study to subdivide absolute teratozoospermia patients by SDF level; this may enable researchers and practitioners to focus on which absolute teratozoospermia patients are the best candidates for ICSI and which should be counselled for SDF treatment prior ICSI and which should be counselled for SDF treatment prior ICSI.